Light trapping in thin silicon solar cells: A review on fundamentals and technologies. (7th June 2021) - Saive, Rebecca
Abstract: Thin, flexible, and efficient silicon solar cells would revolutionize the photovoltaic market and open up new opportunities for PV integration. However, as an indirect semiconductor, silicon exhibits weak absorption for infrared photons and the efficient absorption of the full above bandgap solar spectrum requires careful photon management. This review paper provides an overview on the fundamental physics of light trapping and explains known theoretical limits. Technologies that have been developed to improve light trapping will be discussed, and limitations will be addressed. Abstract : Thin, flexible, and efficient silicon solar cells would revolutionize the photovoltaic market and open up new opportunities for PV integration. However, as an indirect semiconductor, silicon exhibits weak absorption for infrared photons and the efficient absorption of the full above bandgap solar spectrum requires careful photon management. This review paper provides an overview on the fundamental physics of light trapping and explains known theoretical limits.